Dietary methionine affects growth and the expression of key genes involved in hepatic lipogenesis and glucose metabolism in cobia (Rachycentron canadum). (12th November 2019) - Chi, Shuyan; He, Yuanfa; Zhu, Yong; Tan, Beiping; Dong, Xiaohui; Yang, Qihui; Liu, Hongyu; Zhang, Shuang
Abstract: Juvenile cobia ( Rachycentron canadum ), a carnivorous fish, was chosen to examine the effects of methionine (Met) supplementation of low fishmeal diets on growth and the expression of key genes related to hepatic lipogenesis and glucose metabolism. Seven isonitrogenous and isolipidic diets were formulated to contain 7.2, 9.0, 10.0, 12.4, 14.1, 16.3 and 18.6 g/kg dietary Met levels. Healthy cobia (initial average weight ±  SE  = 9.79 ± 0.04 g) were randomly assigned into seven groups in triplicate with 40 individuals per sea cage for 8 weeks. The results showed that the weight gain rate (WGR) of fish increased as the dietary Met was increased up to 12.4 g/kg and then decreased. The expression of insulin‐like growth factor‐I (IGF‐I) and target of rapamycin (TOR) genes was inhibited by the Met‐deficient diets. The mRNA levels of fatty acid synthase (FAS) and sterol regulatory element‐binding protein‐1 (SREBP1) genes increased with increasing dietary Met until 12.4 g/kg after which the former remained constant, whereas the latter decreased from 12.4 to 18.6 g/kg Met. The mRNA levels of pyruvate kinase (PK) increased as the dietary Met levels increased, reaching a peak at 12.4 g/kg, and then decreased with further increases in Met. However, the mRNA levels of phosphoenolpyruvate carboxykinase (PEPCK) decreased as the dietary Met was increased up to 12.4 g/kg and then remained constant from 12.4 to 18.6 g/kg Met. In conclusion, based on the straight broken‐line analysis of WGR against dietary Met levels, the optimal dietary Met requirement for juvenile cobia was estimated to be 12.4 g/kg (26.9 g/kg dietary protein). A diet with the optimal level of Met induces fish growth and is associated with increased IGF‐I and TOR.